Паломничество Ланселота: [роман] / Юлия Вознесенская - Вознесенская Юлия Николаевна (Лепта Книга, 2014)
Экземпляры: ф.18 (20160712) / Инвентарный номер: 545 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: В 64 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44